2016
DOI: 10.1002/hbm.23300
|View full text |Cite
|
Sign up to set email alerts
|

The imaginative mind

Abstract: The astounding capacity for the human imagination to be engaged across a wide range of contexts is limitless and fundamental to our day‐to‐day experiences. Although processes of imagination are central to human psychological function, they rarely occupy center stage in academic discourse or empirical study within psychological and neuroscientific realms. The aim of this paper is to tackle this imbalance by drawing together the multitudinous facets of imagination within a common framework. The processes fall in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 139 publications
1
38
0
4
Order By: Relevance
“…On the other hand, an emerging literature has documented a central role of semantic (Beaty et al, 2014; Benedek et al, 2012b; Kenett et al, 2014, in press) and episodic (Addis et al, 2016; Madore et al, 2015, 2016) memory systems to creative cognition. The present work illustrates how semantic memory can constrain creative thought by activating salient conceptual knowledge during idea generation, but it is clear that memory also benefits creativity by providing acquired knowledge and retrieval mechanisms (Abraham, in press). We think that it is useful to briefly consider our study in the context of this broader literature in order to highlight ways in which memory and creativity may interact.…”
Section: Costs and Benefits Of Memory To Creative Thoughtmentioning
confidence: 81%
“…On the other hand, an emerging literature has documented a central role of semantic (Beaty et al, 2014; Benedek et al, 2012b; Kenett et al, 2014, in press) and episodic (Addis et al, 2016; Madore et al, 2015, 2016) memory systems to creative cognition. The present work illustrates how semantic memory can constrain creative thought by activating salient conceptual knowledge during idea generation, but it is clear that memory also benefits creativity by providing acquired knowledge and retrieval mechanisms (Abraham, in press). We think that it is useful to briefly consider our study in the context of this broader literature in order to highlight ways in which memory and creativity may interact.…”
Section: Costs and Benefits Of Memory To Creative Thoughtmentioning
confidence: 81%
“…The findings of domain-specific studies (e.g., creative writing, visual art making, melody improvisation, etc.) and psychometric tasks 2 highlight the fact that creativity does not rise from a conceptual void but from an ongoing knowledge base development and personal past experiences (Madore et al, 2016;Abraham, 2017). Individuals accumulate a collection of knowledge and routines, which must be both readily accessible and flexibly organized to meet any situational demand.…”
Section: Where Do Creative Ideas Come From?mentioning
confidence: 99%
“…10 A recent proposal, hypothesizing semantic memory as the root of imagination and exhorting to further research in this direction can be found in Abraham and Bubic (2015). An attempt to classify the many functions of imaginations in a unified cognitive model is proposed in Abraham (2016). For the researches on several aspects of the imagination and mental simulation in the field of cognitive sciences, see Markman et alii (2008).…”
Section: Notesmentioning
confidence: 99%